Assessment of selected mangrove sediment properties at Kampung Kuantan - Arselan, Nur Husna (2019)
Mangrove is a unique ecosystem that dominates the line of coast of subtropical and tropical coastlines around the world. It is always referred as carbon sinks as it has capable of storing carbon from the atmosphere and has higher carbon content compared to other forest types. Besides, it also provides habitat for many animals. However, without realizing the importance of this ecosystem, this area had been largely cleared for fisheries, agriculture and development, where it caused this ecosystem to be threatened. Limited amount of data on mangrove ecosystem, especially belowground, has made people unrealised about the potential of the mangroves as carbon storage. Therefore, this study was conducted to provide information and compare the selected mangrove properties at Kampung Kuantan between different plots at two different depths. Data obtained were analysed using the Statistical Analysis System (SAS) version 9.4. Based on the results, the pH in the plot can be classified as moderately acidic. The type of sediment was sandy clay. The results showed there was a significant difference of the total organic carbon between Plot 1 and 5. The total organic carbon was higher at depth 15-30 cm. As a conclusion, sediment properties are important because they may influence the productivity of the mangrove ecosystem. Lastly, as a recommendation, this area of study should be conserved from any activities that would affect the sediment properties.